Intranet system for small and medium-sized organization in Malaysia / Chong Yi Ching - Chong , Yi Ching (2004)
An Intranet system is a company wide-software an information distribution system that uses Internet tools and technology to provide a common multimedia interface within an organization and achieve a better result than the conventional means of data access and transfer. This project is aim at developing an Intranet system for small and medium size organization in Malaysia. It will be develop as enhancement toward the earlier or existing Intranet system used in Malaysia. This Intranet system will target at user who located in managerial executive, and operational level of an organization. There arc six main objective should be achieved by this which are provide tool for employee to manage their time more effectively, create an integrated system, reduce workload and redundant tasks, speed up the data retrieved process, provide cost effective system, and develop a secure web page. The expected outcome of this project will consists of nine main modules, which are login and logout, bulletin board (Announcement) events calendaring, task management, project management, contact directories di cushion forum , fault reporting and knowledge base. Functional requirement for all this modules will be explained in more detail in chapter four (system analysis). It also in Jude, the explanation of the chosen hardware and software that will be used to develop this project. Many research have been don through out this project. All the research will be explained in detail in literature review chapter.